Information on Domestic staff utilisation and household crimes - Attah, Frank M.; Agba, A. M. Ogaboh; Ibiam, Azu A.; Kaburise, Phyllis K.; Kulo, Collins (JINAV: Journal of Information and Visualization, 2021)
Hiring of domestic staff and its effect on households’ crime has been an issues of great concern in Nigeria. This study is sets to investigate the correlates between domestic staff utilisation and crimes such as kidnapping, stealing and rape. Blocked opportunity theory and structural functionalism theory were adopted. Cross-sectional survey design was used while data was generated view questionnaire. A total sample of 330 respondents were selected from households in Southern Senatorial District of Cross River State, Nigeria. Information retrieved were coded and subjected to statistical analysis. Outcome revealed a significant relationship between the hiring of domestic staff and household crimes (such as kidnapping, stealing and rape). It was recommended among others that house helps should be passably screened through proper employment procedures before they are employed as domestic staff.